The Evolution of Islamic Counseling: A Bibliometric Analysis of Trends in Publications from 1981-2023 - Ifdil, Ifdil; Zatrahadi, Fahli; Hasibuan, M Fauzi; Abdullah, Nor Zaiham Midawati; Bah, Yahya Muhammed; Bakar, Abu Yazid Abu; Nurkholidah, Enik (Islamic Guidance and Counseling Journal, 2023)
The objective of Islamic counseling is to focus on incorporating religious values into therapy, offering valuable guidance for individuals who are grappling with psychological and social problems. Therefore, this study aimed to examine the trends in Islamic counseling publications from 1981 to 2023. A qualitative bibliometric method was used to collect data from Scopus database on August 25, 2023. Approximately 244 relevant papers were identified as the sample used for the analysis. Data analysis was conducted using software such as Openrefine-3.6.0, VOSviewer 1.6.18, and Biblioshiny R The results showed that the highest topic trend was recorded in 2020, with 26 citations. Beekun and Badawi held the highest position with a combined score of 281 in terms of publication. Additionally, Rothman, A. and Tahlil, T. were the authors who made significant contributions to the field, each with 4 documents. This study examined 6 clusters, discussing the keywords associated with Islamic counseling. The keywords consisted of the Development of Mental Well-being in Adults through Counseling, Ethics, Morality, and Human Rights in Education and Public Awareness. Furthermore, they included Controlled Human Studies with Gender Type Factors, Treatment of Depression with an Islamic Psychotherapy Approach, Health Services for the Elderly Muslim Community, and Islamism's Influence in Alleviating Poverty through Religious Aspects.